2021
DOI: 10.1093/bjsopen/zraa075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxaliplatin-based chemotherapy on chemosensitivity in patients with peritoneal metastasis from colorectal cancer treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: proof-of-concept study

Abstract: Background Chemosensitivity testing, including collagen gel droplet-embedded culture drug sensitivity test, has proven to be a useful tool in therapeutic decision-making. This retrospective analysis investigated chemosensitivity testing of peritoneal metastases collected during cytoreductive surgery (CRS), and its impact on survival in patients with colorectal cancer. Methods All patients with peritoneal metastasis from color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Furthermore, IV 5-FU is used as only a bolus dose, anticipating a low response rate to oxaliplatin (continuous 48 h 5-FU infusion is today an integral part of oxaliplatin treatment); low duration of heat exposition is unlikely to have any major effect by itself; no study demonstrated a potentiation of oxaliplatin cytotoxicity by heat; and the high rate of postoperative complications may have a negative impact on survival of these metastatic patients. It seems increasingly clear that oxaliplatin-based preoperative SCT, commonly used in PRODIGE 7, can induce a certain degree of tumour resistance, worsening the efficacy of subsequent intraperitoneal oxaliplatin [ 37 ]. PRODIGE 7 included patients with PCI up to 25, when today it is known that cases with PCI > 20 do not benefit from CRS + HIPEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IV 5-FU is used as only a bolus dose, anticipating a low response rate to oxaliplatin (continuous 48 h 5-FU infusion is today an integral part of oxaliplatin treatment); low duration of heat exposition is unlikely to have any major effect by itself; no study demonstrated a potentiation of oxaliplatin cytotoxicity by heat; and the high rate of postoperative complications may have a negative impact on survival of these metastatic patients. It seems increasingly clear that oxaliplatin-based preoperative SCT, commonly used in PRODIGE 7, can induce a certain degree of tumour resistance, worsening the efficacy of subsequent intraperitoneal oxaliplatin [ 37 ]. PRODIGE 7 included patients with PCI up to 25, when today it is known that cases with PCI > 20 do not benefit from CRS + HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“…It seems increasingly clear that oxaliplatin-based preoperative SCT, commonly used in PRODIGE 7, can induce a certain degree of tumour resistance, worsening the efficacy of subsequent intraperitoneal oxaliplatin [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COLOPEC is now the third consecutive clinical trial that has failed to demonstrate efficacy of oxaliplatin-based HIPEC either as an adjuvant treatment or in patients with metastatic CRC, after ProphyloCHIP and PRODIGE 7 109 , 110 . Shared criticisms of these trials are that they all used a short duration of HIPEC of 30 min and used single-agent oxaliplatin, in mainly oxaliplatin pretreated patients, which were proven to be less effective in preclinical models as well as in patient-derived organoids 111 , 112 .…”
Section: Colon Cancermentioning
confidence: 99%
“…More than three-quarters of the patients (85%) have received oxaliplatin-based neoadjuvant chemotherapy (FOLFOX). In a recent study, oxaliplatin chemoresistance was demonstrated in the preoperative setting, potentially making the HIPEC regimen ineffective [21]. Patients who received oxaliplatin before CRS-HIPEC had significantly altered chemosensitivity to this drug.…”
Section: Limitsmentioning
confidence: 99%